Characterization of ovalbumin-carvacrol inclusion complexes as delivery systems with antibacterial application. (August 2020) - Rao, Shengqi; Xu, Guangwei; Lu, Xiangning; Zhang, Ruyi; Gao, Lu; Wang, Qingyan; Yang, Zhenquan; Jiao, Xinan
Abstract: Carvacrol is an effective natural antimicrobial and antioxidant agent; however, its poor aqueous solubility and high volatility limit its application in food systems. Ovalbumin can encapsulate hydrophobic molecules, thereby improving aqueous solubility and reducing volatility. The aim of this study was to explore the potential of an ovalbumin nanocarrier to improve the application range of carvacrol. Protein structure and scanning electron microscopy showed that carvacrol increased gel hardness and tackiness at pH 5, and OVA gel formed a uniform granular shape that was beneficial for reconstitution. The dominant force in OVA gel changed from electrostatic to hydrophobic interaction, indicating that carvacrol could hydrophobically bind to the gel. The ovalbumin-carvacrol (OVA-Car) complex was prepared using an oil-in-water method. The particle size was 132 ± 10 nm, and the encapsulation efficiency was 51.41%. The polydispersity index was 0.355, indicating the general stability of the composite. Fluorescence spectroscopy and differential thermogram studies indicated complex formation. Antibacterial property testing against Bacillus cereus and Salmonella indicated that the OVA-Car complex inhibited bacterial growth at lower concentrations than free carvacrol. Minimum inhibitory concentration and minimum bactericidal concentration for Bacillus cereus (0.0968 and 0.3875 mg/mL) and Salmonella (0.1937 and 0.3875 mg/mL), respectively, were 2–4 times higher than those of free carvacrol. The time sterilization curve indicated that pathogenic bacterial growth did not reach the control level. The OVA-Car complex has potential application in food systems owing to its storage stability and improved antimicrobial activity. Graphical abstract: Image 1 Highlights: As a nanoparticle carrier, ovalbumin improved the application range of carvacrol. The ovalbumin-carvacrol (OVA-Car) complex was stable. OVA-Car complex inhibited bacterial growth more effectively than free carvacrol. The OVA-Car complex has potential application in food systems.